การประยุกต์ใช้ไคโตซานและไคโตซานดัดแปรในการดูดซับน้ำมันหล่อเย็นจากน้ำเสีย - พันธ์ทิพา โห้ใย (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This aim of this research is to study an adsorption of cutting oil on biodegradable adsorbent. The adsorbent used in the work was made from a crustacean shell and called chitosan and modified chitosan. The adsorbents are chitosan bead (C), SDS-modified chitosan (CS), and SDS-Mg(ClO4)2- modified chitosan (CSM). Various parameters, which have an effect on adsorption capacity of cutting oil on adsorbents, were studied here. The parameters are contact time, pH, the initial concentration of cutting oil, dosage of adsorbent, kinds of adsorbent and temperature. All experiments were carried out in series of batch adsorption. The results show that the adsorption capacity of cutting oil on CSM is higher than CS and C, respectively. Equilibrium time is varied with kinds of adsorbents initial concentration of cutting oil. More amount of cutting oil can be adsorbed when the condition is in acidic. Initial concentration of cutting oil and dosage of adsorbent have an effect on adsorption capacity. Adsorption of cutting oil on C, CS, and CSM is an endothermic adsorption. Adsorption isoterm of C and CS fit very well with the Langmuir model while the adsorption isoterm of CSM fit very well with the Freundlich model. The result of thermodynamic elucidates that the adsorption process is spontaneous. The characteristic results also support the experimental results.